Influence of surfactants on Fe2O3 and WO3 nanostructured photoanodes and their photoelectrochemical behaviour - Memar, Amir (Curtin University, 2014)
This study aims to improve photoelectrode performance by varying the nanostructural characteristics of different metal oxides, Fe203 and W03, in a single layer photoanode for photoelectrochemical water splitting application. In this study, we have investigated the effects of various surfactants on photocatalytic activity as well as characterized size of Fe20 3 and W03 nano particles. Furthermore, the effect of surfactant's absorption time and vacant position were investigated and related to the characterized size of nanoparticles.